HUBUNGAN ANTARA PAPARAN ASAP ROKOK DENGAN KEJADIAN INFEKSI SALURAN PERNAPASAN AKUT (ISPA) PADA BALITA DI DESA PUCUNG REJO KABUPATEN MAGELANG, TAHUN 2014 - Wardani, Niken Kusuma; Winarsih, Sri; Sukini, Tuti (UPPM Poltekkes Kememterian Kesehatan, 2015)
Background: smoking is a part of life of the people of Indonesia, the evidence is not difficult to find a person or family with this habit, especially at house. Increase the number of smokers, more people are affected by the smoke who called passive smoking.The impact of cigarette smoke exposure on toddlerhealth include slow lung growth, more susceptible to bronchitis and respiratory tract and ear infections and asthma. Based on the results of interviews with 10 family of toddlers ARI patient members obtained information that 8 of them, the parents are smokers.The purpose of this study : To determine the relationship cigarette smoke exposure in the incidence of Acute Respiratory Infections (ARI) in toddlersat Pucung Rejo Village Magelang Regency.Methods: This study was an analytical study using cross sectional design with a sample of toddler aged 2 months-5 years in Pucung Rejo Village of Magelang Regency as many as 42 toddlers. The data using questionnaires.Results: Based on the analysis results can be seen that p <0.05 and a correlation coefficient calculation 0,537 shows that Correlation Between Cigarette smoke exposure in the incidence of Acute Respiratory Infections (ARI) in toddlersat Pucung Rejo Village Magelang Regency with moderate strength.Conclusions and suggestions: Most of toddlers get smoke exposure and experience ARI not pneumonia.The author expects that parents eliminate the habit of smoking or smokers who have children are expected to not smoke around children or inside the house which also contained a toddler.